Canagliflozin alleviates valproic acid-induced autism in rat pups: Role of PTEN/PDK/PPAR-γ signaling pathways - Elgamal, Mariam A.; Khodeer, Dina M.; Abdel-Wahab, Basel A.; Ibrahim, Ibrahim Abdel Aziz; Alzahrani, Abdullah R.; Moustafa, Yasser M.; Ali, Azza A.; El-Sayed, Norhan M. (Frontiers in Pharmacology, 2023)
Autism is complex and multifactorial, and is one of the fastest growing neurodevelopmental disorders. Canagliflozin (Cana) is an antidiabetic drug that exhibits neuroprotective properties in various neurodegenerative syndromes. This study investigated the possible protective effect of Cana against the valproic acid (VPA)-induced model of autism. VPA was injected subcutaneously (SC) into rat pups at a dose of 300 mg/kg, twice daily on postnatal day-2 (PD-2) and PD-3, and once on PD-4 to induce an autism-like syndrome. Graded doses of Cana were administered (5 mg/kg, 7.5 mg/kg, and 10 mg/kg, P.O.) starting from the first day of VPA injections and continued for 21 days. At the end of the experiment, behavioral tests and histopathological alterations were assessed. In addition, the gene expression of peroxisome proliferator-activated receptor γ (PPAR γ), lactate dehydrogenase A (LDHA), pyruvate dehydrogenase kinase (PDK), cellular myeloctomatosis (c-Myc) with protein expression of glucose transporter-1 (GLUT-1), phosphatase and tensin homolog (PTEN), and level of acetylcholine (ACh) were determined. Treatment with Cana significantly counteracted histopathological changes in the cerebellum tissues of the brain induced by VPA. Cana (5 mg/kg, 7.5 mg/kg, and 10 mg/kg) improved sociability and social preference, enhanced stereotypic behaviors, and decreased hyperlocomotion activity, in addition to its significant effect on the canonical Wnt/β-catenin pathway via the downregulation of gene expression of LDHA (22%, 64%, and 73% in cerebellum tissues with 51%, 60%, and 75% in cerebrum tissues), PDK (27%, 50%, and 67% in cerebellum tissues with 34%, 66%, and 77% in cerebrum tissues), c-Myc (35%, 44%, and 72% in cerebellum tissues with 19%, 58%, and 79% in cerebrum tissues), protein expression of GLUT-1 (32%, 48%, and 49% in cerebellum tissues with 30%, 50%, and 54% in cerebrum tissues), and elevating gene expression of PPAR-γ (2, 3, and 4 folds in cerebellum tissues with 1.5, 3, and 9 folds in cerebrum tissues), protein expression of PTEN (2, 5, and 6 folds in cerebellum tissues with 6, 6, and 10 folds in cerebrum tissues), and increasing the ACh levels (4, 5, and 7 folds) in brain tissues. The current study confirmed the ameliorating effect of Cana against neurochemical and behavioral alterations in the VPA-induced model of autism in rats.